Using input-output analysis to estimate the regional economic impact of universities: a case study - Santos, Sérgio Pereira dos (2014)
The role of higher education institutions in the economic development of the areas where they are located has long been recognised and its quantification has been the subject of analysis of several studies over the past three decades. In spite of the interest in this area of research, there is no universally accepted methodology for evaluating their impact. It is the main objective of this paper to contribute to the study of this theme through the discussion of some of the fundamental methodological aspects underlying the use of the input-output analysis in the evaluation of the economic impact of higher education institutions. This discussion is illustrated and supported by a case study in one of Portugal’s newer universities, the University of Algarve. Based on the input-output analysis, it was estimated that in 2003/04 the direct economic impact of the University of Algarve in the regional economy exceeded 75 million Euros. This direct impact was estimated to result in a total economic impact of around 100 million Euros, and consequently, in a multiplier effect of 1,34. In terms of employment, it was estimated that around 2370 jobs in the region are dependent of the University of Algarve, including 1360 directly employed by the university.